2020
DOI: 10.1186/s12576-020-00747-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypericum scabrum extract on dentate gyrus synaptic plasticity in high fat diet-fed rats

Abstract: High-fat diet (HFD) can induce deficits in neural function, oxidative stress, and decrease hippocampal neurogenesis. Hypericum (H.) scabrum extract (Ext) contains compounds that could treat neurological disorders. This study aimed to examine the neuroprotective impacts of the H. scabrum Ext on hippocampal synaptic plasticity in rats that were fed HFD. Fifty-four male Wistar rats (220 ± 10 g) were randomly arranged in six groups: (1) HFD group; (2) HFD + Ext300 group; (3) HFD + Ext100 group; (4) Control group; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 85 publications
0
8
0
Order By: Relevance
“…HS extract is a powerful source of antioxidant on the account of its composition. Omidi et al (2020) determined that HS contains flavonoids such as quercitrin and quercetin that can scavenge the free radicals. Previous studies revealed that TPC amount of microcapsule is quite high when compared with its extract form.…”
Section: Resultsmentioning
confidence: 99%
“…HS extract is a powerful source of antioxidant on the account of its composition. Omidi et al (2020) determined that HS contains flavonoids such as quercitrin and quercetin that can scavenge the free radicals. Previous studies revealed that TPC amount of microcapsule is quite high when compared with its extract form.…”
Section: Resultsmentioning
confidence: 99%
“…LTP data were normalized to the mean value of fEPSP slopes and PS amplitude recorded before LTP induction (Equation 3 ). 43 , 51 , 52 p ‐values less than 0.05 were regarded as significant. …”
Section: Methodsmentioning
confidence: 99%
“…Oxidative stress is responsible for the pathogenesis of several diseases, including memory deficits caused by oxidative damage in rats and humans. The brain undergoes severe damage under oxidative stress due to the abundance of unsaturated fatty acids, lower antioxidant protection, redox-active metals (Fe, Cu), and high oxygen concentrations [7,23,29].…”
Section: The Production Of Free Radicalsmentioning
confidence: 99%
“…However, AD treatment via antioxidants is met with great suspicion, as most of them can hardly cross the BBB. Accordingly, smaller antioxidant molecules or non-toxic carriers can provide favorable modifications for the current complications [25,26,29].…”
Section: Antioxidant Systemsmentioning
confidence: 99%